Dietary nitrate supplementation effect on dynamic cerebral autoregulation in normoxia and acute hypoxia. Issue 3 (March 2022) - Horiuchi, Masahiro; Rossetti, Gabriella MK; Oliver, Samuel J
We tested the hypothesis that increasing the nitric oxide (NO) bioavailability by dietary nitrate would recover the hypoxia-induced reduction in dynamic cerebral autoregulation (CA). Twelve healthy males (age 21 ± 2 years) completed four days of dietary supplementation with a placebo or inorganic nitrate drink (140-ml beetroot juice per day) followed by 60-min of normoxia or hypoxia (fraction of inspired oxygen [FiO2 ] = 13%). Duplex ultrasonography was used to perform volumetric change-based assessment of dynamic CA in the internal carotid artery (ICA). Dynamic CA was assessed by rate of regulation (RoR) of vascular conductance using the thigh-cuff method. Four days of beetroot supplementation increased circulating nitrate by 208 [171, 245] μM (mean difference [95% confidence interval]) compared with placebo. Dynamic CA was lower in hypoxia than normoxia (RoR Δ−0.085 [−0.116, −0.054]). Compared with placebo, nitrate did not alter dynamic CA in normoxia (RoR Δ−0.022 [−0.060, 0.016]) or hypoxia (RoR Δ0.017 [−0.019, 0.053]). Further, nitrate did not affect ICA vessel diameter, blood velocity or flow in either normoxia or hypoxia. Increased bioavailability of NO through dietary nitrate supplementation did not recover the hypoxia-induced reduction in dynamic CA. This suggests the mechanism of hypoxia-induced reduction in dynamic CA does not relate to the availability of NO.